Therapeutic Hypothermia in Severe Neonatal Hypoxic-Ischemic Encephalopathy: A Case Report and Literature Review - Yantri, Eny; Zulfahmi, Zulfahmi (Health and Medical Journal, 2026)
Hypoxic-ischemic encephalopathy (HIE) remains a leading cause of neonatal mortality and long-term neurodevelopmental disability worldwide, with therapeutic hypothermia emerging as the standard neuroprotective intervention for eligible neonates with moderate to severe HIE. We report a case of a late preterm female neonate (36-37 weeks gestation) born via emergency cesarean section due to severe maternal preeclampsia with respiratory failure, who presented with severe birth asphyxia (APGAR scores 1/3), profound metabolic acidosis (umbilical cord pH 6.7, base excess -20 mmol/L), and severe encephalopathy (Thompson score 15). Therapeutic hypothermia was initiated within 6 hours of birth and continued for 72 hours, followed by controlled rewarming, with the patient requiring mechanical ventilation for 10 days and hospitalization for 17 days total. The patient demonstrated progressive neurological improvement with Thompson scores decreasing from 15 to 3 over the first four days of treatment, while cerebral regional oxygen saturation remained within normal limits throughout cooling therapy. The infant was successfully weaned from mechanical ventilation, achieved full enteral feeding, and was discharged home without apparent neurological sequelae. This case demonstrates the successful implementation of evidence-based therapeutic hypothermia protocols in severe HIE management, emphasizing that early recognition, appropriate patient selection, precise temperature control, and comprehensive supportive care are critical for optimal outcomes, while long-term neurodevelopmental follow-up remains essential for all HIE survivors.